Cryptophytes as potential source of natural antimicrobials for food preservation - Abidizadegan, Maryam; Peltomaa, Elina; Ilina, Polina; Tammela, Päivi; Blomster, Jaanika (Frontiers in Microbiology, 2024)
Cryptophytes are a promising source of bioactive compounds that have not been fully explored. This research investigated the antimicrobial activity of total phenolic compounds (TPC) and exopolysaccharides (EPS) extracted from several cryptophytes against a range of harmful foodborne bacteria and fungi. To measure the minimum inhibitory concentration (MIC) value, the broth microdilution method was used. In the antibacterial evaluation of TPC, the MIC ranged between 31.25 and 500 µg/ml, while for the antifungal activity test, it varied from 31.25 to 125 µg/ml. In the antibacterial activity test of EPS, the MIC values ranged from 125 to 1000 µg/ml, whereas in the antifungal susceptibility test, it ranged between 62.5 and 1000 µg/ml. The most resistant pathogen against TPC was Escherichia coli, while Campylobacter jejuni was the most susceptible. In the case of EPS, the most resistant pathogen was Salmonella Typhimurium, while Aspergillus versicolor exhibited the highest susceptibility. Overall, in terms of antimicrobial activity, TPC was more effective than EPS. Finally, the tolerance level (TL) for TPC and EPS was ≤4 in all tested samples, indicating their bactericidal/fungicidal mechanism of action. In conclusion, TPC and EPS isolated from cryptophytes demonstrated remarkable antimicrobial properties and ability to fully eradicate pathogens, and could be considered as natural preservatives in the food industry.